Meeting the Needs of Parents of Children With Scoliosis: A Qualitative Descriptive Study - Leanne R. Willson; Laura G. Rogers; Nicole Gingrich; Kathleen Shearer; Sarah Southon Hryniuk (SAGE Publishing, 2021)
Needs of parents with children with scoliosis are complex and depend on their child's treatments. The purpose of this study was to identify needs of parents with children with scoliosis. This qualitative description involved interviews with parents of children at various stages of treatment. A convenience, then purposeful sample of 16 parents (12 mothers, two fathers, and two stepfathers) was interviewed; interviews were transcribed and analyzed using thematic analysis. Parents' needs included: Needing reliable medical information; Desiring information on complementary treatments; Wanting help in supporting and advocating for their child; Needing to protect the child and family; and Seeking connection and support. Although many parents' needs are being met, this study recommends a nursing role aimed at providing parents with reliable medical information, discussing alternative treatments, assisting parents in their role of supporting their child, helping parents in their advocacy efforts, and referring parents to appropriate connections.